2004
DOI: 10.1007/s11661-004-1007-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and modeling of cleavage fracture in simulated heat-affected zone microstructures of a high-strength low alloy steel

Abstract: The effect of the welding cycle on the fracture toughness properties of high-strength low alloy (HSLA) steels is examined by means of thermal simulation of heat-affected zone (HAZ) microstructures. Tensile tests on notched bars and fracture toughness tests at various temperatures are performed together with fracture surface observations and cross-sectional analyses. The influence of martensite-austenite (M-A) constituents and of "crystallographic" bainite packets on cleavage fracture micromechanisms is, thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(114 citation statements)
references
References 30 publications
6
107
0
1
Order By: Relevance
“…20,21) The predictions of all the models were however limited to a unique steel, so that the applicability to the steels having different distributions of microstructures was not covered.…”
Section: D Observation Of Micro-cracks As Cleavage Fracture Initiatimentioning
confidence: 99%
“…20,21) The predictions of all the models were however limited to a unique steel, so that the applicability to the steels having different distributions of microstructures was not covered.…”
Section: D Observation Of Micro-cracks As Cleavage Fracture Initiatimentioning
confidence: 99%
“…Influence of grain boundaries in cleavage fracture (a) Introduction: material GBs in ferritic steels offer an important resistance to the propagation of cleavage cracks, particularly in the DBT regime (e.g. the pioneering work by Hahn et al [41] who showed cleavage cracks arrested at GBs and, more recently, the work by Lambert-Perlade et al [42] who showed using acoustic emission that cracks could be arrested at GBs or packet boundaries). Based on further observations in hydrogen-charged Fe-3% Si alloy, Gell & Smith [43] demonstrated that the resistance of GBs to the transmission of cleavage cracks across them was governed more significantly by the twist misorientation than the tilt misorientation.…”
Section: Ii) Partial Dislocationsmentioning
confidence: 99%
“…Recently, a few studies on the characterization of brittle cracks using EBSD have been reported. [14,[16][17][18][19][20] However, initiation and propagation of cleavage cracks in the HAZ of high strength (e.g. X100) have not been explored to the best of our understanding.…”
Section: Thermo-mechanically Processed X80-x100mentioning
confidence: 99%